PENGARUH LITERASI KEUANGAN SYARIAH DAN PENGETAHUAN INVESTASI TERHADAP KEPUTUSAN BERINVESTASI PADA MAHASISWA MANAJEMEN KEUANGAN SYARIAH UNIVERSITAS ISLAM NEGERI JAMBI - Diana Putri, Nopi; Subhan, Muhammad; Hareastoma (Program Studi Manajemen Keuangan Syariah, 2026)
This study aims to examine the influence of Islamic financial literacy and investment knowledge on the investment decisions of students in the Islamic Financial Management Study Program at the State Islamic University of Sulthan Thaha Saifuddin Jambi. The research background highlights the low level of Islamic financial literacy among students and their limited understanding of Sharia-based investment principles, which may affect their decision-making. This research employs a quantitative approach with a causal associative method. The population consists of 508 students, and a sample of 84 respondents was selected using the Slovin formula with a 10% margin of error. Data were collected through questionnaires and analyzed using multiple linear regression, t-test, and F-test. The results indicate that Islamic financial literacy has a positive and significant effect on students’ investment decisions when tested partially. Similarly, investment knowledge also shows a positive and significant partial effect. Simultaneously, both variables significantly influence investment decisions. These findings highlight the need to enhance students’ understanding of Islamic finance and investment principles to encourage prudent, Sharia-compliant investment behavior. This research can serve as a reference for curriculum development and Islamic financial education that is more practical and applicable within academic environments.